Phenotypic variants among ethyl methanesulfonate M2 mutant lines in Capsicum annuum. (16th July 2014) - Hwang, Doyeon; Jeong, Hee-Jin; Kwon, Jin-Kyung; Kim, Hohyun; Kang, Si-Yong; Kang, Byoung-Cheorl
Abstract : Induction of mutations using chemical mutagens has proved to be a useful tool in crop improvement and has advantages over transgenic approaches in view of legislative restrictions and intellectual property. Among the chemical mutagens, ethyl methanesulfonate (EMS) has been widely used to generate novel traits. In this study, we constructed an EMS mutant population consisting of 3945 M2 mutant lines using a Korean landrace of Capsicum annuum 'Yuwol-cho'. In total, 1480 M2 mutant lines were evaluated for novel traits. The mutant lines showed phenotypic variations such as plant growth (small size and dwarfism), development of leaves (variegation, colour and morphological changes), flowers (inflorescence, morphological and organ colour changes), and fruits (morphological and colour changes). Most of these mutant phenotypes were inherited recessively. Many of the mutant phenotypes were unique in pepper, while some were similar to those of known mutants in other plant species. These mutant lines will be useful for the study of gene function in C. annuum .